Organizational form as a solution to the problem of credible commitment: The evolution of naming strategies among U.S. hotel chains, 1896-1980 - Ingram, Paul (Strategic Management Journal, 2007)
This paper describes how organizational form can solve the problem of commitment that complicates exchange. I illustrate this by analyzing the commitment problem of hotel chains. Consideration of the commitment problem indicates that hotel chains are better off naming their units the same, so as to create the potential for future business from customers. However, some hoteliers believed units should be named differently so they are not identified with the chain. These two strategies illustrate a powerful tension between strategies that allow the organization to be more consistent, and strategies that facilitate adaptation to local conditions. I analyze the failure rates of hotel chains to show that selection favored chains that employed the naming strategy that generates commitment.